2021
DOI: 10.1016/j.seppur.2021.119283
|View full text |Cite
|
Sign up to set email alerts
|

Selective and enhanced nickel adsorption from sulfate- and calcium-rich solutions using chitosan

Abstract: Highlights• Chitosan effectively adsorbed Ni from a real Ni/Ca/SO4 2bearing leachate • Sulfate had a positive effect on Ni adsorption while Ca did not have any effect• Formation of NiSO4 0 species contributed to the enhanced Ni adsorption onto chitosan • Chitosan has a Ni qmax of 1.49 mmol/g even with 500 mM SO4 2and 10 mM Ca present • Chitosan was selective for Ni over Ca as validated in a column setup ABSTRACT Nickel (Ni) is an economically important metal characterized by its mechanical strength and anticor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The formation of the unloaded sample is shown in the range of 800-1200 cm − 1 by a complex group of absorption bands. The strong peak at 1059 cm-1 appearing in both CS-Ca and loaded nanocomposites was generally ascribed to the saccharide framework of the chitosan, also coincided with the vibration of Ca-O linkage through the chitosan matrix [37].…”
Section: Ftir Studymentioning
confidence: 84%
“…The formation of the unloaded sample is shown in the range of 800-1200 cm − 1 by a complex group of absorption bands. The strong peak at 1059 cm-1 appearing in both CS-Ca and loaded nanocomposites was generally ascribed to the saccharide framework of the chitosan, also coincided with the vibration of Ca-O linkage through the chitosan matrix [37].…”
Section: Ftir Studymentioning
confidence: 84%
“…9e), and N 1s spectrum includes two peaks N-H (401.45 eV) and C-N-C (399.51 eV) (Fig. 9f) [26] . After modification with TA and Fe 3+ , a weak Fe signal peak appeared at 702.94 eV.…”
Section: Xpsmentioning
confidence: 96%
“…In addition, compared with zein-Fe III , zein-CQDs-Fe III and zein-PTN-Fe III , the curves of zein-PTN-CQDs-Fe III nanoparticles showed a new small peak at 58.72°. The emergence of new peaks indicated that intermolecular interactions occured between FeCl 3 , TA, zein, PTN and CQDs, and the intermolecular interactions changed the physical states of each substance before the reaction [26] . The above results indicated that zein-PTN-CQDs nanoparticles could be formed by adding FeCl 3 and TA based on intermolecular interaction.…”
Section: Xrdmentioning
confidence: 99%
“…The interaction of heavy metal cations, e.g., Cd 2+ , with biological components typically contributes to surface functional groups, e.g., hydroxyl and carboxyl groups (-COOH at 1737 cm -1 and -OH at 3334 cm -1 , as shown in Fig. 1) (Nicomel et al 2021). The sorbed coexisting cadmium on the surface groups of the RRB provided extra sorption sites for PHE through n-π interactions, resulting in synergistic sorption for PHE (Xiao et al 2007).…”
Section: Sorption Performance Of Rice Root Biomass (Rrb) In Single An...mentioning
confidence: 99%